Supply response of agriculture in the argentinean economy - Herrou Aragón, Alberto (2005)
In the paper by A. Herrou-Aragón (2001), it was found that the tax on the volume of international trade in the Argentinean economy was about 110 percent in the second half of the 80s and about 55 percent during the 90s compared to that of the second half of the 30s. The commercial policies leading to the heavy taxation of international trade during the second half of the 80s have certainly harmed, to some extent, the growth potential of the Argentinean exportable sector during those years. This paper is aimed at estimating the extent to which taxation of international trade has had an impact on the Argentinean agricultural sector during the period from 1939 until 1984 for which the needed data is available.